2020
DOI: 10.3389/fpsyg.2020.00514
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urban/Rural Environments on Mexican Children’s Connection to Nature and Pro-environmental Behavior

Abstract: Living in rural areas has been described a driver for behaving in a pro-environmental way, mainly due to the more frequent contact with nature that people from rural areas have. However, the processes that link living in a rural area and behaving in a more ecological manner have not been systematically studied. Moreover, most studies have focused on adults living in developed countries. Given the importance that the actions conducted by people in developing countries have for the future of the environment, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
(61 reference statements)
3
20
0
3
Order By: Relevance
“…CN is thought to be one of the main factors leading to PEB (Tam 2013;Frantz and Mayer 2014;Gkargkavouzi et al 2018) and, as such, there is a growing interest on the factors leading to CN (Di Fabio and Kenny 2018;. For example, experiences in nature (e.g., nature-based recreation) are seen as a relevant determinant of CN (Duron-Ramos et al 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…CN is thought to be one of the main factors leading to PEB (Tam 2013;Frantz and Mayer 2014;Gkargkavouzi et al 2018) and, as such, there is a growing interest on the factors leading to CN (Di Fabio and Kenny 2018;. For example, experiences in nature (e.g., nature-based recreation) are seen as a relevant determinant of CN (Duron-Ramos et al 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…The research documents positive relationships between nature connection, attachment to place, and personal environmental behaviors, including support for conservation [11][12][13][14].…”
Section: Introductionmentioning
confidence: 92%
“…A recent study investigated the factors that account for pro-ecological behaviors, and found that nature connectedness, nature experiences (time spent in nature and nature engagement) and nature-based knowledge and attitudes explained 70% of the variation in people's actions for nature (Richardson et al, 2020). Other studies have shown that connectedness to nature and frequency of visits to nature is linked to pro-ecological behaviors (Collado et al, 2015;Duron-Ramos et al, 2020). Recent work suggested that outdoor nature experiences can help overcome fears of "creepy crawlies" such as insects and snakes and can help develop respectful and positive attitudes toward nature (Hosaka et al, 2017;Chawla, 2020).…”
Section: Introductionmentioning
confidence: 99%